Comparison of three single-passage SAHs with different modifications - Ayyad, Shadi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: The increasing costs of fossil fuels and the influence of their harmful combustion products on the climate change, which has dramatically been revealed in this century are considered as critical dynamics behind the global search for different suggestions to meet these urgent challenges. In the present work, three different types of solar air heaters (SAHs). One of the collector consist of fins attached to aluminum plate and the other collectors made of two different sizes of aluminum square tubes as absorber plates were experimentally investigated in order to achieve the most efficient design of the proposed SAHs. Experiments were conducted, based on the ASHRAE standards, under Famagusta - Cyprus climatic conditions. The thermal performances of the three collectors were examined over a broad range of operating and design conditions. Results showed that there was no superiority for one collector over the other. The effect of mass flow rate on the performance was different for each SAH. At low mass flow rates it was found that the SAH having 20 x 20 mm square aluminum tubes as absorber plate has the highest efficiency which was calculated as 86%; whereas, the maximum efficiency at higher mass flow rates was obtained in the SAH having finned absorber plate which was 93%. Key words: Solar air heater, Thermal efficiency, Collectors, Temperature, Panels. ………………………………………………………………………………………………………………………… ÖZ: Fosil yakıtların fiyatlarındaki artış ve yanma sonucu ortaya çıkan zaralı bileşiklerin iklim değişikliği üzerindeki etkileri global olarak başka acil çözümler aranması üzerinde önemli dinamikler teşkil etmektedir. Bu çalışmada üç değişik tipte Havalı Güneş Isıtıcıları (HGI) finli düz ve iki değişik ölçüde kare alüminyum profiller emici yüzey olarak en verimli tasarımı belirlemek için deneylerde kullanılmışlardır. Deneyler Kıbrıs – Mağusa koşulları altında, ASHRAE standartlarına göre yürütülmüştür. Kollektörlerin ısıl performansları geniş bir işletme ve tasarım aralığı üzerinde incelenmiştir. Sonuçlar her üç tipin de birbiri üzerine büyük bir üstünlük sağlamadığını göstermiştir. Hava akış oranının her bir tasarım üzerindeki etkisi farklı olmuştur. Düşük hava akış oranlarında 20 x 20 mm ölçüsündeki aluminyum kollektörün %86‟lık en yüksek verimi verdiği hesaplanmıştır. En yüksek verim ise fin tipi emici plakası olan kollektör tarafından %93 olarak yüksek hava akış oranlarında elde edilmiştir. Anahtar kelimeler: Güneş hava ısıtıcı, Isıl verim, Collectors, paneller, Sıcaklık.
Master of Science in Mechanical Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2013. Supervisor: Assoc. Prof. Dr. Hasan Hacışevki.
Keywords: Ayyad; Shadi